The Bayesian Contrast of Clinical Events and the Evidence Quantitative Method in Chronic Disease Research - Cristian Antony Ramos Vera (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Bayesian statistics make it possible to contrast statistical hypotheses of significance through probabilities, a priori and posteriori, given the data, whose usefulness is ideal in clinical research. One of the best-known methods is the Bayes factor. The application of this Bayesian method is an alternative to evaluate comparative hypotheses of investigations with binary data, effective for case-control studies. The statistical application using the Bayesian test can be very useful in other research related to COVID-19 that can methodologically reinforce future investigations of chronic diseases of greater interest to Finlay magazine.